Perla carantana - a new species of the genus Perla (Plecoptera: Perlidae) from Austria and Slovenia - Ignac Sivec; Wolfram Graf (Natura Sloveniae)
Members of the genus Perla are the largest, and amongst the most endangered European stonefly species. During a revisionary study of this genus, a new species was discovered at several localities in Austria and Slovenia; Perla carantana was named after Carantania, a 7th - 11th century political unit within the territories of Austria and Slovenia. Adults and larvae are nearly indistinguishable from the sympatric species, Perla burmeisteriana Claassen, but the two species can be clearly distinguished on the basis of egg chorion morphology.